Morphological characteristics of DISH in patients with OPLL and its association with high-sensitivity CRP: inflammatory DISH. (1st February 2022) - Nguyen, Tran Canh Tung; Yahara, Yasuhito; Yasuda, Taketoshi; Seki, Shoji; Suzuki, Kayo; Watanabe, Kenta; Makino, Hiroto; Kamei, Katsuhiko; Mori, Kanji; Kawaguchi, Yoshiharu
Abstract: Objectives: To characterize and clarify evidence as to whether the ectopic bone formations of DISH in patients with ossification of the posterior longitudinal ligament (OPLL) are caused by inflammatory or degenerative processes. Methods: Whole-spine CT and serum high-sensitivity CRP (hs-CRP) levels were obtained from 182 cervical OPLL patients (DISH+, n  = 104; DISH−, n  = 78). In the DISH+ group, ectopic bone formations were categorized into Flat and Jaggy types, then further divided into three subgroups: group 1 (Jaggy-dominant pattern), group 2 (Equivalence of pattern) and group 3 (Flat-dominant pattern). Data were compared between the DISH+ and DISH− groups, and among the three subgroups. Results: The upper thoracic spine was most affected by the Flat type, whereas the Jaggy type was more frequent in the middle and lower thoracic regions. There was no difference in hs-CRP levels between the DISH+ and DISH− groups. Among the three subgroups, hs-CRP levels in group 3 [mean (s .d .) 0.16 (0.09) mg/dl] were significantly higher than in group 1 [0.04 (0.02) mg/dl] and group 2 [0.08 (0.06) mg/dl]. Higher levels of hs-CRP were associated with a greater number of vertebral units with Flat-type formations ( β  = 0.691, P < 0.0001) and with a lesser number of vertebral units with Jaggy-type formations ( β  = −0.147, P  = 0.036). Conclusion: The Flat type in DISH might be caused by an inflammatory pathogenesis rather than a degenerative process presented in the Jaggy type.